INCOME OPPORTUNITIES FOR THE UEB CENTRAL ARGEO MARTÍNEZ CONTRIBUTION IN CO2 EMISSIONS REDUCTION - Dupuy Parra, José Rolando; Álvarez Blanco, Andrés; Videaux Aguilar, Mairelis; Lesme Jaén, René (Centro Azúcar Journal, 2021)
Introduction: In the Central Argeo Martínez UEB, an average of 890 kWh of clean energy is generated annually in the last nine harvests from sugarcane bagasse residues. Nevertheless, its commercialization due CO2 no longer emitted into atmosphere is not determined. Objective: To evaluate the amount of CO2 and the income that the entity loses for this concept. Materials and Methods: To analyze all results, a balance of power grid delivery for clean energy generation was used, and the European CO2 negotiation system was taken into account, which in studied period was $ 67.75. Results and Discussion: As a result, it was obtained that a total of 12419948 g CO2 were no longer emitted into atmosphere, its represents a total of 12858446.25 $-g CO2 in studied period. Conclusions: The Argeo Martínez power plant has generated 8,014 kWh of clean energy from cane bagasse waste in the last nine harvests, which represents 0.06% of the consumption of the national electrical energy system. In this time, it stopped emitting 12,419,948 g CO2 into the atmosphere; this represents 12,858,446.25 $–g CO2 according to European business system CO2 value.